Normal Human Gingival Epithelial Cells Sense C. parapsilosis by Toll-Like Receptors and Module Its Pathogenesis through Antimicrobial Peptides and Proinflammatory Cytokines - Raouf Bahri; Sèverine Curt; Dalila Saidane-Mosbahi; Mahmoud Rouabhia (Mediators of Inflammation)
This study was designed to investigate the interaction between C. parapsilosis and human epithelial cells using monolayer cultures and an engineered human oral mucosa (EHOM). C. parapsilosis was able to adhere to gingival epithelial cells and to adopt the hyphal form in the presence of serum. Interestingly, when cultured onto the engineered human oral mucosa (EHOM), C. parapsilosis formed small biofilm and invaded the connective tissue. Following contact with C. parapsilosis, normal human gingival epithelial cells expressed high levels of Toll-like receptors (TLR)-2, -4, and -6, but not TLR-9 mRNA. The upregulation of TLRs was paralleled by an increase of IL-1β, TNFα, and IFNγ mRNA expression, suggesting the involvement of these cytokines in the defense against infection with C. parapsilosis. The active role of epithelial cells in the innate immunity against C. parapsilosis infection was enhanced by their capacity to express high levels of human beta-defensin-1, -2, and -3. The upregulation of proinflammatory cytokines and antimicrobial peptide expression may explain the growth inhibition of C. parapsilosis by the gingival epithelial cells. Overall results provide additional evidence of the involvement of epithelial cells in the innate immunity against C. parapsilosis infections.